Boundary-value problem with impulsive action for a parabolic equation with degeneration - Pukalskyi, I. D.; Yashan, B. O. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.984.54 For a second-order parabolic equation, we consider a problem with oblique derivative and impulsive action. The coefficients of the equation and the boundary condition have power singularities of any order in the time and space variables on some set of points. We establish conditions for the existence and uniqueness of the solution of the problem in Hölder spaces with power weight.